Presidents' Day - Rockwell, Anne F.; Rockwell, Lizzy (New York : Harper, 2008)
Mrs. Madoff's preschool class learns about President's Day and puts on a play about the men who inspired the holiday, particularly those featured on Mount Rushmore.
Wilson's Children, January 2009
School Library Journal, January 2008
Book Links (A.L.A.), December 2008
Booklist, February 2008
Horn Book, October 2008
2.7
Keywords: Presidents' Day -- Juvenile fiction; Schools -- Juvenile fiction; Presidents' Day -- Fiction; Schools -- Fiction; Presidents' Day -- Fiction; School stories; Picture books for children